Pre-lithiated silicon-oxygen composite negative electrode material and preparation method and application thereof

CN123002858APending Publication Date: 2026-10-30HUAZHONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611205740.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有技术的以上缺陷或改进需求,本发明提供了一种预锂化硅氧复合负极材料的制备方法,旨在解决现有预锂化过程中由于残碱问题影响环境稳定性和水系加工适配性,从而影响极片性能的技术问题

Benefits of technology

1、本发明提供的预锂化硅氧复合负极材料的制备方法通过将包碳硅氧粉末加入到钛酸丁酯溶液中搅拌反应,形成在碳包覆硅氧材料表面包覆二氧化钛的前驱层溶液,然后在后续预锂化过程中实现硅氧基体内部预锂化的同时,外层的二氧化钛原位转化为具有氧缺陷的含锂钛基保护层。区别于传统的事后物理混合除碱手段,采用事前防御与原位同步转化的策略,从源头上阻断了残碱的生成与累积,显著提高了材料的环境稳定性,能够有效解决匀浆过程中的产气与凝胶问题。此外,原位生成的具有氧缺陷的Li-Ti-O层兼具优异的物理屏障作用与良好的离子电导率,在保障材料高容量和高首次充放电效率的前提下,大幅提升了其性能

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002858A_ABST
    Figure CN123002858A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery negative electrode materials, and relates to a pre-lithiated silicon-oxygen composite negative electrode material and a preparation method and application thereof. The method comprises the following steps: adding carbon-coated silicon-oxygen powder into a butyl titanate solution, stirring and reacting to obtain a carbon-coated silicon-oxygen precursor solution, wherein the carbon-coated silicon-oxygen precursor is coated with an amorphous titanium dioxide layer on the surface; after heating and drying, a carbon-coated silicon-oxygen precursor is obtained; and the precursor is mixed with lithium hydride to perform pre-lithiation treatment, so as to obtain a pre-lithiated silicon-oxygen composite negative electrode material. The pre-lithiated silicon-oxygen composite negative electrode material prepared by the method has low residual alkali and excellent stability, and also has good electrochemical performance. When the pre-lithiated silicon-oxygen composite negative electrode material is prepared into a battery, there is almost no degradation phenomenon caused by residual alkali.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode material technology, and more specifically, relates to a pre-lithiated silicon-oxygen composite anode material, its preparation method, and its application. Background Technology

[0002] With the rapid development of the electric vehicle and energy storage industries, the market demand for the energy density of lithium-ion batteries continues to increase. The theoretical specific capacity of existing commercial graphite anodes is approximately 372 mAh / g, which is close to the upper limit for practical applications, making it difficult to significantly improve battery energy density further. Therefore, developing novel anode materials with high specific capacity has become a key focus for the industry.

[0003] Silicon-based anode materials (including Si and SiO) x Silicon-oxygen materials (SO4) possess advantages such as high theoretical specific capacity, low operating potential, abundant resources, and environmental friendliness, making them important candidates for next-generation high-energy-density lithium-ion battery anode materials. Among them, SO4 materials typically offer advantages over pure silicon materials, including smaller volume expansion, relatively better cycle stability, and easier process scaling, demonstrating strong industrialization potential. However, because SO4 materials contain oxygen, they readily consume a large amount of active lithium during the first charge-discharge cycle, resulting in a low initial coulombic efficiency and limiting their practical application in high-energy-density batteries.

[0004] To address this issue, existing technologies typically employ pre-lithiation methods for lithium replenishment to compensate for the initial irreversible capacity loss. Current industrial-scale pre-lithiation technologies mainly include solid-phase pre-lithiation and liquid-phase pre-lithiation. Regarding solid-phase pre-lithiation, CN201911046597.2 discloses a typical scheme, which involves blending a highly active lithium source (such as metallic lithium or lithium hydride) with a carbon-coated silicon-oxygen composite material and heating it under an inert atmosphere to complete pre-lithiation, thereby improving the material's initial charge-discharge efficiency. Regarding liquid-phase pre-lithiation, CN201910208184.3 provides a liquid-phase lithium replenishment scheme, which involves first dissolving metallic lithium in a specific organic solvent to form a pre-lithiation solution, and then reacting it with the negative electrode powder to achieve a more uniform lithiation process and improve the initial efficiency.

[0005] However, the aforementioned existing technologies still have significant drawbacks in practical engineering applications. In particular, the residual alkali problem during pre-lithiation affects environmental stability and compatibility with aqueous processing, thus impacting the performance of the final electrode. Specifically, during pre-lithiation, the reaction between the lithium source and silicon-oxygen materials generates lithium-containing silicates and other products, accompanied by significant volume changes, easily causing cracking of the outer carbon coating layer. Once cracks or gaps appear in the carbon layer, the lithium-containing active components in the material are easily further converted into strongly alkaline residues such as LiOH and Li2CO3 in air or humid environments. During subsequent aqueous slurry preparation, a large amount of this residual alkali dissolves, making the slurry highly alkaline, typically resulting in pH > 11, which in turn leads to problems such as binder failure, slurry sedimentation, and corrosion of the copper current collector. As the outer lithium-containing phase continuously reacts with and dissolves in water, the internal highly active silicon matrix is ​​further exposed to the aqueous phase, easily leading to hydrogen evolution side reactions, resulting in gas generation in the homogenized slurry, decreased electrode coating quality, and reversible capacity decay. Summary of the Invention

[0006] In view of the above-mentioned defects or improvement needs of the existing technology, the present invention provides a method for preparing pre-lithiated silicon-oxygen composite anode material, which aims to solve the technical problem that the residual alkali in the existing pre-lithiation process affects the environmental stability and water system processing compatibility, thereby affecting the performance of the electrode.

[0007] To achieve the above objectives, in one aspect of the present invention, a method for preparing a pre-lithiated silicon-oxygen composite anode material is provided, comprising the following steps: S1: Carbon-coated silicon oxide powder is added to a tetrabutyl titanate solution and stirred to obtain a carbon-coated silicon oxide precursor solution. The surface of the carbon-coated silicon oxide precursor is covered with a layer of amorphous titanium dioxide. After heating and drying, the carbon-coated silicon oxide precursor is obtained. S2: The precursor is mixed with lithium hydride and pre-lithiation is performed to obtain a pre-lithiated silicon-oxygen composite anode material.

[0008] Preferably, the mass-to-volume ratio of the carbon-coated silicon oxide powder to the tetrabutyl titanate solution is 10 mg / μL to 40 mg / μL.

[0009] Preferably, the tetrabutyl titanate solution is an anhydrous ethanol solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to anhydrous ethanol is 0.83 μL / mL to 3.33 μL / mL.

[0010] Preferably, in step S1, carbon-coated silicon oxide powder is added to an anhydrous ethanol solution of tetrabutyl titanate, ultrasonically mixed, and then stirred in an open container to obtain a carbon-coated silicon oxide precursor solution.

[0011] Preferably, the ultrasound time is 0.5 h to 1 h, and the stirring time is 12 h to 36 h.

[0012] Preferably, the carbon-coated silicon oxide powder is carbon-coated silicon oxide.

[0013] Preferably, the molar ratio of lithium hydride to carbon-coated silicon oxide powder is 0.2 to 1.0.

[0014] Preferably, in step S2, the pre-lithiation treatment specifically involves heating to 700 ℃~800 ℃ at a heating rate of 2 ℃ / min~5 ℃ / min under a protective atmosphere and holding at that temperature for 6 h~10 h.

[0015] In another aspect of the present invention, a pre-lithiated silicon-oxygen composite anode material prepared according to any one of the above-described preparation methods is provided.

[0016] In another aspect of the present invention, a silicon-oxygen composite negative electrode sheet is provided, which is made of the pre-lithiated silicon-oxygen composite material as described above.

[0017] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages: 1. The preparation method of the pre-lithiated silicon-oxygen composite anode material provided by this invention involves adding carbon-coated silicon-oxygen powder to a tetrabutyl titanate solution and stirring to form a precursor layer solution with titanium dioxide coated on the surface of the carbon-coated silicon-oxygen material. Then, during the subsequent pre-lithiation process, while the silicon-oxygen matrix is ​​pre-lithiated internally, the outer titanium dioxide layer is in-situ transformed into a lithium-titanium-based protective layer with oxygen defects. Unlike traditional post-processing physical mixing and alkali removal methods, this method employs a strategy of pre-processing defense and in-situ simultaneous transformation, blocking the generation and accumulation of residual alkali at the source, significantly improving the environmental stability of the material, and effectively solving the problems of gas generation and gelation during the homogenization process. Furthermore, the in-situ generated Li-Ti-O layer with oxygen defects possesses both excellent physical barrier properties and good ionic conductivity, significantly improving the material's performance while ensuring high capacity and high initial charge-discharge efficiency. 2. In this invention, the preferred mass-to-volume ratio of carbon-coated silicon oxide powder to tetrabutyl titanate in the tetrabutyl titanate solution is 10 mg / μL to 40 mg / μL to ensure the thickness and integrity of the amorphous titanium dioxide coating layer on the precursor surface. If the ratio is below 10 mg / μL (i.e., tetrabutyl titanate is excessive), the coating layer will be too thick, consuming too much active lithium to generate a lithium-containing titanium matrix phase in the subsequent high-temperature solid-state reaction, leading to a decrease in reversible capacity; at the same time, the excessively thick coating increases the resistance to lithium-ion transport, affecting rate performance. If the ratio is above 40 mg / μL (i.e., tetrabutyl titanate is insufficient), the coating layer will be too thin or discontinuous, failing to effectively isolate moisture and residual alkali, resulting in limited improvement in the material's environmental stability. By controlling the concentration within the range of 10–40 mg / μL, a continuous, dense, and moderately thick TiO2 precursor layer can be formed. After pre-lithiation in situ, it is transformed into an oxygen-deficient Li-Ti-O protective layer. This layer not only physically blocks external moisture from contacting the internal active lithium, reducing residual alkali formation, but also possesses good ionic conductivity without sacrificing capacity and first-efficiency performance, achieving the optimal balance between protective effect and electrochemical performance. 3. In this invention, the preferred solution of tetrabutyl titanate is an anhydrous ethanol solution of tetrabutyl titanate. Anhydrous ethanol is used as a dilution and dispersion medium for tetrabutyl titanate. By reducing the initial water content of the system, its rapid hydrolysis is inhibited and the dispersion of the precursor is improved, thereby improving the uniformity of the surface coating.

[0018] 4. The pre-lithiated silicon-oxygen composite anode material of this invention exhibits low residual alkali and excellent stability, while also possessing good electrochemical performance. When used in battery fabrication, it exhibits virtually no degradation caused by residual alkali. Therefore, this composition is suitable for preparing pre-lithiated silicon-oxygen anode materials with high stability and excellent electrochemical performance, and can be applied to high-energy-density lithium-ion battery systems, especially suitable for the preparation and application of silicon-oxygen anode materials in power batteries, energy storage batteries, and high-energy-density consumer electronics batteries. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the modified pre-lithiated silicon oxide precursor before and after pre-lithiation, as exemplified by the present invention.

[0020] Figure 2 The X-ray diffraction (XRD) patterns of the precursor SiO@C@TiO2 involved in step (2) of Embodiment 2 of the present invention and SiO@C of Comparative Example 1 after treatment at 500°C.

[0021] Figure 3 The images show the XRD patterns of the pre-lithiated silicon-oxygen composite anode materials involved in Embodiment 2, Comparative Example 1, and Comparative Example 5 of this invention.

[0022] Figure 4 These are scanning electron microscope (SEM) images of Embodiment 2 and Comparative Example 5 of the present invention.

[0023] Figure 5 This is a transmission electron microscope (TEM) mapping image of the pre-lithiated silicon-oxygen composite anode material precursor prepared in Example 2 of the present invention.

[0024] Figure 6 The cycling curves are those of the silicon-oxygen composite anode materials prepared in Example 2, Comparative Example 1, and Comparative Example 5 of this invention.

[0025] Figure 7 Gas generation test of the silicon-oxygen composite anode material prepared in Example 2 and Comparative Example 5 of this invention. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0027] To achieve the above objectives, the following solutions are provided: In a first aspect of the present invention, a method for preparing a pre-lithiated silicon-oxygen composite anode material is provided, comprising the following steps: S1: Add carbon-coated silicon oxide powder to a tetrabutyl titanate solution and mix. Stir the mixture to allow the tetrabutyl titanate in the solution to undergo hydrolysis and condensation to obtain a carbon-coated silicon oxide precursor solution. The carbon-coated silicon oxide precursor is coated with a layer of amorphous titanium dioxide. Heat and dry the carbon-coated silicon oxide precursor solution to obtain the precursor. S2: A pre-lithiated silicon-oxygen composite anode material is obtained by mixing a carbon silicon-oxygen precursor with lithium hydride and performing pre-lithiation treatment.

[0028] Figure 1 The diagram shows the structure of the modified pre-lithiated silicon-oxygen precursor before and after pre-lithiation provided by the method of the present invention. As can be seen from the figure, SiO@C coated with TiO2 undergoes volume expansion during high-temperature solid-state pre-lithiation, causing cracks to appear in the original carbon layer. The gaps expose active lithium substances. The TiO2 layer not only better ensures the integrity of the material surface but also reacts with the active lithium substances to generate a Li-Ti-O protective layer with oxygen defects, achieving surface coating and residual alkali conversion during the pre-lithiation process.

[0029] Preferably, the mass-to-volume ratio of carbon-coated silica powder to tetrabutyl titanate in the tetrabutyl titanate solution is 10 mg / μL to 40 mg / μL; more preferably 20 mg / μL.

[0030] Preferably, the solvent in the tetrabutyl titanate solution is anhydrous ethanol. Anhydrous ethanol serves as the dilution and dispersion medium for tetrabutyl titanate. The gradual introduction of moisture from the air into the system slows the hydrolysis rate, reducing the rapid formation of independent TiO2 particles in the solution. This allows titanium species to more readily nucleate heterogeneously on the SiO@C surface and form a uniform coating layer. Simultaneously, the Ti-O-Ti network is difficult to fully crystallize at room temperature; therefore, the resulting coating is typically amorphous or hydrated amorphous TiO2. The volume ratio of tetrabutyl titanate to anhydrous ethanol is 0.83 μL / mL to 3.33 μL / mL.

[0031] Preferably, in step S1, carbon-coated silica powder is added to an anhydrous ethanol solution of tetrabutyl titanate, and ultrasonication is used to fully disperse the particles and uniformly wet and adsorb the tetrabutyl titanate onto the particle surface. Subsequently, the mixture is stirred in an open container, allowing the anhydrous ethanol to gradually absorb moisture from the air. This absorbed moisture causes the tetrabutyl titanate in the solution to undergo hydrolysis and condensation, coating the carbon-coated silica surface with a layer of amorphous titanium dioxide, thus obtaining a carbon-coated silica precursor solution. The ultrasonication time is 0.5 h to 1 h, the stirring time is 12 h to 36 h, and the stirring temperature is room temperature.

[0032] Preferably, in step S1, the reacted solution is heated and stirred to promote solvent evaporation and removal of residual tetrabutyl titanate. After evaporation to dryness, it is then vacuum dried to obtain the precursor (SiO@C@TiO2). For example, the stirring temperature is 50 ℃~60 ℃, the drying temperature is 60 ℃~80 ℃, and the drying time is 8 h~12 h, which can further remove surface residues.

[0033] Preferably, the carbon-coated silicon oxide powder is a core-shell structured silicon-based composite anode material, specifically carbon-coated silicon oxide, and more preferably carbon-coated silicon monoxide.

[0034] Preferably, in step S2, the precursor obtained in step S1 is mixed with lithium hydride, ground uniformly, and placed in a tube furnace with an inert gas atmosphere for high-temperature solid-state reaction. After cooling, a pre-lithiated silicon-oxygen composite anode material (SiO@C@LTO) is obtained. Specifically, under an argon atmosphere, the temperature is increased to 700℃~800℃ at a heating rate of 2℃ / min~5℃ / min, and held for 6h~10h.

[0035] Preferably, the molar ratio of lithium hydride to carbon-coated silicon oxide is 0.20~1.00, and the grinding method is mortar and pestle grinding.

[0036] According to another aspect of the present invention, a method for preparing a pre-lithiated silicon-oxygen composite anode material is provided. The pre-lithiated silicon-oxygen anode material prepared by this method is a silicon-oxygen anode material containing a lithium titanium-based protective layer, which has low residual alkali and excellent stability, and also has good electrochemical performance.

[0037] According to another aspect of the present invention, a silicon-oxygen composite negative electrode sheet is provided, which is made of the pre-lithiated silicon-oxygen composite material as described above.

[0038] According to another aspect of the present invention, a lithium-ion battery is provided, comprising the silicon-oxygen composite negative electrode sheet described above. This lithium-ion battery exhibits almost no degradation caused by residual alkali, and its capacity does not suddenly and rapidly decrease during subsequent cycles.

[0039] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings.

[0040] The carbon-coated silicon oxide powder used in the following examples was prepared by the following steps: placing silicon monoxide (5 μm ~ 10 μm) in a CVD furnace, introducing methane, and sintering at high temperature to obtain a 5 wt% carbon-coated silicon oxide material. Figure 2 As shown in the XRD characterization test diagram of SiO@C, it can be seen that carbon-coated silicon monoxide powder SiO@C was successfully prepared.

[0041] Example 1: This embodiment provides a pre-lithiated silicon-oxygen composite anode material, the preparation method of which is as follows: (1) First, dissolve tetrabutyl titanate in anhydrous ethanol solution and sonicate for half an hour. Take 30 mL of the tetrabutyl titanate ethanol solution into a reagent bottle and add 1 g of carbon-coated silica powder (the volume ratio of tetrabutyl titanate to anhydrous ethanol in the tetrabutyl titanate ethanol solution is 0.83 μL / mL, and the corresponding mass-volume ratio of carbon-coated silica powder to tetrabutyl titanate in the tetrabutyl titanate solution is 40 mg / μL). Continue sonicating for half an hour to disperse the powder evenly. Place the reagent bottle open and stir at room temperature for 24 h under normal conditions.

[0042] (2) Subsequently, the powder was heated and stirred at 60°C to remove ethanol and residual tetrabutyl titanate. Finally, the powder was dried in a vacuum oven at 60°C for 8 h to obtain the precursor SiO@C@TiO2.

[0043] (3) SiO@C@TiO2 and lithium hydride are mixed at a molar ratio of 1:0.66, ground evenly, and placed in a tube furnace with inert gas for high-temperature solid-phase reaction at 750 °C for 8 h. After cooling to room temperature, pre-lithiated silicon-oxygen composite anode material is obtained.

[0044] Example 2: The pre-lithiated silicon-oxygen composite anode material was denoted as LSiO@C@LTO. The preparation steps were the same as in Example 1, except that in step (1), the volume ratio of tetrabutyl titanate to anhydrous ethanol in the tetrabutyl titanate ethanol solution was 1.67 μL / mL, and the corresponding mass-volume ratio of carbon-coated silicon monoxide powder to tetrabutyl titanate in the tetrabutyl titanate solution was 20 mg / μL.

[0045] Example 3: The preparation steps are the same as in Example 1, except that in step (1), the volume ratio of tetrabutyl titanate to anhydrous ethanol in the ethanol solution is 3.33 μL / mL, and the corresponding mass-volume ratio of carbon-coated silica powder to tetrabutyl titanate in the solution is 10 mg / μL.

[0046] Comparative Example 1: This comparative example uses untreated carbon-coated silicon monoxide powder SiO@C from the previous examples.

[0047] Comparative Example 2: This comparative example uses untreated SiO@C as raw material, and pre-lithiation is carried out directly through high-temperature solid-state reaction to obtain pre-lithiated material. The preparation method includes: mixing SiO@C and lithium hydride at a molar ratio of 1:0.20, grinding evenly, placing in a tube furnace with inert gas for high-temperature solid-state reaction at 750°C for 8 h, and cooling to room temperature to obtain the final product.

[0048] Comparative Example 3: The preparation steps were the same as those in Comparative Example 2, except that the molar ratio of SiO@C to lithium hydride was 1:0.33.

[0049] Comparative Example 4: The preparation steps were the same as those in Comparative Example 2, except that the molar ratio of SiO@C to lithium hydride was 1:0.50.

[0050] Comparative Example 5: The pre-lithiated silicon-oxygen composite anode material was denoted as LSiO@C. The preparation steps were the same as those in Comparative Example 2, except that the molar ratio of SiO@C to lithium hydride was 1:0.66.

[0051] Comparative Example 6: The preparation steps were the same as those in Comparative Example 2, except that the molar ratio of SiO@C to lithium hydride was 1:0.80.

[0052] Comparative Example 7: The preparation steps were the same as those in Comparative Example 2, except that the molar ratio of SiO@C to lithium hydride was 1:1.00.

[0053] Characterization and testing: The morphology of the substances in the above embodiments and comparative examples was characterized as follows: Figure 2 The XRD patterns of the precursor SiO@C@TiO2 from step (2) of Example 2 and the untreated carbon-coated silicon monoxide powder SiO@C after treatment at 500°C are shown. To ensure clear observation of characteristic peaks in the XRD test, the precursor SiO@C@TiO2 from step (2) of Example 2 is referred to as SiO@C@TiO2-50 μL TBOT, and the precursor obtained by increasing the amount of tetrabutyl titanate to 75 μL in step (2) of Example 2 is referred to as SiO@C@TiO2-75 μL TBOT. When the amount of tetrabutyl titanate is small, SiO@C@TiO2-50 μL TBOT does not have obvious TiO2 signal peaks. When the amount of tetrabutyl titanate is increased, obvious diffraction peaks can be observed at 25.3° and 48.0°, which correspond to the (101) and (200) crystal planes of anatase TiO2, respectively. These diffraction peaks can be well indexed to anatase TiO2 (PDF#21-1272).

[0054] Figure 3 The XRD patterns of the pre-lithiated silicon-oxygen composite anode material LSiO@C@LTO prepared in Example 2, SiO@C prepared in Comparative Example 1, and LSiO@C prepared in Comparative Example 5 are shown. The figures show that after pre-lithiation of SiO@C in Comparative Example 1 to obtain LSiO@C in Comparative Example 5, in addition to the original Si (PDF#78-2500) diffraction peaks, Li2SiO3 (PDF#29-0829) diffraction peaks also appear, indicating that the main lithium silicate salt phase formed after pre-lithiation is Li2SiO3. However, the SiO@C@TiO2 in Example 2 does not show obvious titanium lithium oxide peaks after pre-lithiation. Further combining... Figure 4 The images show the SEM images of the pre-lithiated silicon-oxygen composite anode material LSiO@C@LTO prepared in Example 2 and the LSiO@C prepared in Comparative Example 5. As can be seen from the images, the surface of the uncoated LSiO@C in Comparative Example 5 is relatively rough, with obvious irregular particle adhesion and local agglomeration, indicating that more reaction products were generated on the sample surface after TiO2 coating and pre-lithiation, resulting in a relatively non-uniform surface state. In contrast, the surface morphology of the sample in Example 2 after TiO2 coating and pre-lithiation changed significantly. The LSiO@C@LTO sample has a more complete overall particle outline, and the surface is covered with a layer of fine and relatively uniform granular structure. The roughness is significantly lower than that of LSiO@C, indicating that the thinner coating layer can form a certain protective conversion layer on the material surface during the pre-lithiation process.

[0055] Figure 5This is a TEM mapping image of the modified pre-lithiated silicon oxide precursor in Example 2. The image shows that the TiO2 layer coating on LSiO@C@LTO is relatively uniform, demonstrating overall particle coating.

[0056] The substances from the above examples and comparative examples were subjected to pH, gas production, and performance tests, as follows: The pre-lithiated silicon-oxygen composite anode materials prepared in Examples 1-3 were compared with the SiO@C of Comparative Example 1 and the anode materials prepared in Comparative Examples 2-7 for pH, gas generation and charge-discharge performance tests.

[0057] For charge / discharge performance testing, 120 mg of silicon oxide powder, 15 mg of conductive agent Super P, and 375 mg of PAA-Li (4% solid content) were added to a homogenizing tube, homogenized using a micro-vibrating ball mill, and then coated onto copper foil. The mixture was dried at 80 °C for 12 h to obtain a silicon oxide electrode. A 2032 coin cell was assembled in the following order: negative electrode shell, spring, gasket, lithium sheet, Celgard 2325 separator, silicon oxide electrode, and positive electrode shell. 1.2 mol / L lithium hexafluorophosphate (LiPF6) as the lithium salt and 5 wt% fluoroethylene carbonate (FEC) as an additive were added to an electrolyte of ethylene carbonate (EC) / diethyl carbonate (DEC) (mass ratio = 1:1). The charge / discharge voltage range of the battery was 0.01 V ~ 1.50 V. Cyclic testing was performed on a Newway charge / discharge instrument at a test temperature of 30 °C.

[0058] For pH testing, 0.3 g of the products from Examples 1-3 and Comparative Examples 2-7 were dispersed in 30 mL of deionized water and stirred continuously. The pH value was tested after stirring for 30 min. For gas production testing, the products from Examples 1-3 and Comparative Examples 2-7, PAA-Li, and super P were weighed in a ratio of 8:1:1 and mixed into a slurry. 1 g of the slurry was placed in a 10 mL syringe with a stopper, and the piston rod position was adjusted so that the initial pusher position was at the 1 mL mark. The pusher position was observed visually after 6 h.

[0059] Table 1: Performance test results of the negative electrode materials in the embodiments and comparative examples of the present invention

[0060] The test results are shown in Table 1 above.

[0061] The pH values ​​of Comparative Examples 2–7 were 10.79, 11.06, 11.21, 11.47, 12.31, and 12.55, respectively, generally increasing with the degree of pre-lithiation. Example 1, being a non-pre-lithiated material, did not undergo corresponding alkalinity testing. The test results show that with increasing pre-lithiation, the amount of residual alkaline lithium species on the material surface gradually increases, exacerbating the residual alkali problem in the pre-lithiated silicon-oxygen composite material. In the gas production test, Comparative Examples 2–4, due to their lower pre-lithiation, did not show significant gas production within 6 hours; Comparative Example 5 produced 2 mL of gas, indicating a certain degree of gas production; Comparative Examples 6 and 7 produced well over 10 mL of gas, essentially pushing the piston rod to the top in less than 2 hours, indicating a very vigorous gas production reaction. These test results indicate that with continuously increasing pre-lithiation, residual alkaline lithium species appear on the material surface, and this increase continues. Residual alkali species readily react with water to generate gas during aqueous processing, leading to slurry bubbling and deterioration of rheological properties, which is detrimental to electrode processing.

[0062] From an electrochemical performance perspective, Comparative Example 1, without pre-lithiation, exhibited an initial coulombic efficiency of only 75.04% and a 50-cycle capacity retention of only 48.1%, indicating significant initial irreversible lithium loss and cycle degradation in unlithiated SiO@C. With increasing pre-lithiation levels, the initial coulombic efficiencies of Comparative Examples 2–5 increased to 81.67%, 84.03%, 89.35%, and 90.45%, respectively, demonstrating that moderate pre-lithiation can effectively compensate for irreversible lithium consumption during the initial cycle. However, while Comparative Examples 6 and 7 still achieved initial coulombic efficiencies of 86.49% and 84.20%, respectively, their pH values ​​rose to 12.31 and 12.55, accompanied by severe gas generation. Simultaneously, their 50-cycle capacity retention decreased to 60.7% and 54.6%, respectively, indicating that excessive pre-lithiation introduces excessive residual alkali and highly active lithiated components, thereby exacerbating interfacial side reactions and impairing cycle stability.

[0063] Considering the initial coulombic efficiency, 50-week capacity retention, alkalinity, and gas production of Comparative Examples 2–5, Comparative Example 5, while achieving an initial coulombic efficiency of 90.45% and a 50-week capacity retention of 77.1%, exhibited some residual alkali and approximately 2 mL of gas production, but did not show the severe processing risks exhibited by Comparative Examples 6 and 7. Therefore, the pre-lithiation ratio corresponding to Comparative Example 5 strikes a relatively reasonable balance between lithium replenishment effect and processing feasibility, and thus this pre-lithiation ratio was selected as the basis for subsequent surface modification and process optimization studies.

[0064] Examples 1-3 and Comparative Example 5 used the same or similar degree of pre-lithiation, therefore their initial coulombic efficiencies were generally at a comparable level. The initial coulombic efficiencies of Examples 1-3 were 90.07%, 92.80%, and 89.75%, respectively, while Comparative Example 5 was 90.45%, indicating that surface modification did not significantly weaken the lithium replenishment effect of the pre-lithiated material. Among them, Example 2 had the highest initial coulombic efficiency, reaching 92.80%.

[0065] Compared to the unmodified Comparative Example 5, the pH values ​​of Examples 1-3 decreased from 11.47 to 11.28, 10.96, and 10.82, respectively, indicating that the modified layer can consume or fix residual active lithium and alkaline species such as LiOH and Li2CO3 on the material surface, effectively alleviating the residual alkali problem of the pre-lithiated material. Correspondingly, the gas production of Comparative Example 5 was 2 mL within 6 h, while the gas production of Example 1 decreased to 1 mL, and no significant gas production was observed in Examples 2 and 3. This demonstrates that the surface modified layer constructed in this invention can reduce the direct contact between the pre-lithiated silicon-oxygen composite material and water, and inhibit the side reactions between active lithium species and water, thereby significantly reducing hydrogen generation during the processing of aqueous slurries.

[0066] The reduction in residual alkali and gas production can further improve the storage and rheological stability of the slurry, reduce slurry bubbling and defects such as pinholes, cracks, local delamination, and uneven surface density after coating, which is beneficial to improving the consistency of electrode coating, drying, and rolling processes. At the same time, the stable surface modification layer can also reduce the continuous side reactions between the material and the electrolyte, and inhibit the repeated breakage and reconstruction of unstable interfaces. Therefore, the 50-cycle capacity retention rates of Examples 1-3 reached 89.5%, 94.8%, and 93.6%, respectively, which were significantly higher than the 77.1% of Comparative Example 5, indicating that the modification treatment can significantly improve the cycle stability of the pre-lithiated silicon-oxygen composite anode material.

[0067] Further comparison of Examples 1-3 reveals differences in the degree of coating of the modified layers. Example 1 exhibits relatively insufficient surface modification layer coating, resulting in weaker isolation and fixation of active lithium and alkaline species. Consequently, its pH remains at 11.28, and approximately 1 mL of gas is still generated within 6 hours. Its 50-week capacity retention rate of 89.5% is also lower than that of Examples 2 and 3. Examples 2 and 3 demonstrate better coating integrity, with pH values ​​decreasing to 10.96 and 10.82 respectively, and no significant gas production was observed, indicating a more significant inhibitory effect on residual alkali and moisture side reactions.

[0068] The modified layer coating in Example 1 was not complete, and the reaction forming the modified layer still consumed a certain amount of active lithium. Therefore, its initial coulombic efficiency was slightly lower than that of Example 2. Although Example 3 had a lower pH and good gas production suppression effect, its modified layer was relatively thick, which consumed more active lithium during pre-lithiation and modification, and may increase interfacial transport resistance. Therefore, its initial coulombic efficiency was 89.75%, slightly lower than 92.80% of Example 2. Example 2 ensured the continuity and integrity of the modified layer while avoiding insufficient protection due to an excessively thin coating layer and additional active lithium consumption due to an excessively thick coating layer. It had a pH of 10.96, no obvious gas production, an initial coulombic efficiency of 92.80%, and a 50-cycle capacity retention of 94.8%, showing the best overall balance between lithium replenishment effect, residual alkali control, processing stability, and cycle performance. Therefore, the coating amount or modifier addition ratio corresponding to Example 2 is the preferred condition.

[0069] Figure 6 The cycling curves of SiO@C in Comparative Example 1 and LSiO@C in Comparative Example 5 are shown for the modified pre-lithiated silicon oxide in Example 2. At a current of 0.1 A / g, the initial charge / discharge specific capacity of SiO@C is 1422.46 / 1895.64 mAh / g, with an initial coulombic efficiency of 75.04%; the initial charge / discharge specific capacity of LSiO@C with a ratio of 0.66 is 1242.69 / 1376.51 mAh / g, with an initial coulombic efficiency of 90.45%; and the initial discharge specific capacity of LSiO@C@LTO is 1295.01 / 1395.41 mAh / g, with an initial coulombic efficiency of 92.80%. These results indicate that the formation of the Li-Ti-O layer on the surface of LSiO@C@LTO did not affect the initial efficiency. Cycling performance was tested at 1 A / g. As shown in the figure, SiO@C exhibited poor cycling performance, retaining only 30.17% of its capacity after 99 cycles at 1 A / g. LSiO@C showed some improvement, with relatively stable capacity for the first 30 cycles, but then rapidly declining. This was mainly due to the residual alkaline substances generated after pre-lithiation damaging the electrode, resulting in a capacity retention of only 45.81%. LSiO@C@LTO showed better cycling performance than LSiO@C, with better capacity retention in subsequent cycles, achieving a capacity retention of 73.31% after 100 cycles.

[0070] In summary, this invention obtains a precursor by pre-coating a titanium dioxide layer on the surface of a carbon-coated silicon oxide material, and then mixes the precursor with a lithium source for high-temperature solid-state heat treatment. During the pre-lithiation heat treatment, pre-lithiation is achieved inside the silicon oxide matrix, while the outer titanium dioxide layer is in-situ transformed into a lithium-titanium-based protective layer with oxygen vacancies. This invention differs from traditional post-treatment physical mixing and alkali removal methods by employing a strategy of pre-treatment and in-situ simultaneous transformation, blocking the generation and accumulation of residual alkali at the source, significantly improving the environmental stability of the material, and solving the problems of gas generation and gelation during homogenization. Furthermore, the in-situ generated Li-Ti-O layer with oxygen vacancies possesses both excellent physical barrier properties and good ionic conductivity, significantly improving the material's performance while ensuring high capacity and high first charge / discharge efficiency.

[0071] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a pre-lithiated silicon-oxygen composite anode material, characterized in that, Includes the following steps: S1: Carbon-coated silicon oxide powder is added to a tetrabutyl titanate solution and stirred to obtain a carbon-coated silicon oxide precursor solution, wherein the surface of the carbon-coated silicon oxide precursor is coated with a layer of amorphous titanium dioxide. After heating and drying, a carbon-coated silicon-oxygen precursor was obtained. S2: The carbon-coated silicon-oxygen precursor is mixed with lithium hydride and pre-lithiation is performed to obtain a pre-lithiated silicon-oxygen composite anode material.

2. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 1, characterized in that, The mass-to-volume ratio of the carbon-coated silica powder to the tetrabutyl titanate solution is 10 mg / μL to 40 mg / μL.

3. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 2, characterized in that, The tetrabutyl titanate solution is an anhydrous ethanol solution of tetrabutyl titanate, wherein the volume ratio of tetrabutyl titanate to anhydrous ethanol is 0.83 μL / mL to 3.33 μL / mL.

4. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 3, characterized in that, In step S1, carbon-coated silicon oxide powder is added to an anhydrous ethanol solution of tetrabutyl titanate, ultrasonically mixed, and then stirred in an open container to obtain a carbon-coated silicon oxide precursor solution.

5. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 4, characterized in that, The ultrasound duration is 0.5 h to 1 h, and the stirring duration is 12 h to 36 h.

6. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 1, characterized in that, The carbon-coated silicon oxide powder is carbon-coated silicon oxide.

7. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 1, characterized in that, The molar ratio of lithium hydride to carbon-coated silicon oxide powder is 0.2 to 1.

0.

8. The method for preparing the pre-lithiated silicon-oxygen composite anode material according to claim 1, characterized in that, In step S2, the pre-lithiation treatment specifically involves heating to 700℃~800℃ at a heating rate of 2℃ / min~5℃ / min under a protective atmosphere and holding at that temperature for 6h~10h.

9. The pre-lithiated silicon-oxygen composite anode material prepared by the preparation method of the pre-lithiated silicon-oxygen composite anode material according to any one of claims 1-8.

10. A silicon-oxygen composite negative electrode sheet, characterized in that, It is prepared using the pre-lithiated silicon oxide composite material as described in claim 9.

Citation Information

Patent Citations

  • Pre-lithiation method for negative electrode material of lithium-ion battery

    CN110010863A

  • Negative electrode material and preparation method thereof and lithium ion battery

    CN112751027A